(untitled) (Eurasian Medical Research Periodical, 2023)
On the basis of the Republican Specialized Scientific and Practical Medical Center for Dermatology and Venereology of the Ministry of Health of the Republic of Uzbekistan, later in the department of the Fergana Regional Dermatology and Venereal Diseases Dispensary No. 2 in the city of Kokand, as well as in the departments of the Fergana Regional Dermatology and Venereal Diseases Dispensary No. 1 in the city of Fergana, 100 patients with psoriasis (men - 60 people, women - 40 people) aged 18 to 72 years were examined. Based on the results of the study, the article discusses the issues of studying the significance of psychotherapeutic and psychopharmacotherapeutic treatment of neurotic disorders in patients with various forms of psoriasis, which will significantly increase the therapeutic effectiveness of the methods of therapy used, as well as lengthen the terms of clinical remission, which will be reflected in the quality of life of patients.